Association of future cancer metastases with fibroblast activation protein-α: a systematic review and meta-analysis - Janani, Majid; Poorkhani, Amirhoushang; Amiriani, Taghi; Donyadideh, Ghazaleh; Ahmadi, Farahnazsadat; Jorjanisorkhankalateh, Yalda; Beheshti-Nia, Fereshteh; Kalaei, Zahra; Roudbaraki, Morad; Soltani, Mahsa; Khori, Vahid; Alizadeh, Ali Mohammad (Frontiers in Oncology, 2024)
Introduction: Fibroblast activation protein-α (FAP-α) is a vital surface marker of cancerassociated fibroblasts, and its high expression is associated with higher tumor grade and metastasis. A systematic review and meta-analysis were performed to associate future metastases with FAP-α expression in cancer.In our meta-analysis, relevant studies published before February 20 th , 2024, were systematically searched through online databases including PubMed, Scopus, and Web of Science. The association between FAP-α expression and metastasis, including distant metastasis, lymph node metastasis, vessel invasion, vascular invasion, and neural invasion was evaluated. A pooled Odds Ratio (OR) with 95% confidence intervals (CI) was reported as a measure of association.Twenty-eight studies with 3,188 patients were included in the present systematic review and meta-analysis. The random effect model for five parameters showed that high FAP-α expression was associated with vessel invasion (OR: 3.04, 95% CI: 1.54-5.99, I 2 =63%, P=0.001), lymph vessel invasion (OR: 3.56, 95% CI: 2.14-5.93, I 2 =0.00%, P <0.001), lymph node metastasis (OR: 2.73, 95% CI: 1.96-3.81, I 2 =65%, P <0.001), and distant metastasis (OR: 2.59; 95% CI: 1.16-5.79, I 2 =81%, P <0.001). However, our analysis showed no statistically significant association between high FAP-α expression and neural invasion (OR: 1.57, 95% CI: 0.84-2.93, I 2 =38%, P=0.161).Conclusions: This meta-analysis indicated that cancer cells with high FAP-α expression have a higher risk of metastasis than low FAP-α expression. These findings support the potential importance of FAP-α as a biomarker for cancer metastasis prediction.